A comparative analysis of the clinical and genomic characteristics of Panton–Valentine leukocidin–positive methicillin-resistant Staphylococcus aureus in Korea and Japan - Hiroshi Kaneko; Eu Suk Kim; Shiho Yokomori; Wan Beom Park; Jongtak Jung; Song Mi Moon; Kyoung-Ho Song; Jeong Su Park; Taek Soo Kim; Yuji Hirai; Hiroshi Maruyama; Mitsuhiro Kamimura; et al. (Microbiology Spectrum, 2026)
ABSTRACT Panton – Valentine leukocidin (PVL) is a leukocyte-lytic toxin produced by Staphylococcus aureus , which is primarily associated with skin and soft tissue infections. Notably, there has been an increase in the number of cases caused by the USA300 lineage in Japan. However, the reported prevalence of USA300 is limited in other Asian countries, including Korea. This study investigated the prevalence of PVL-positive methicillin-resistant S. aureus (MRSA) in Korea and Japan and compared their molecular epidemiological characteristics. A total of 463 MRSA strains were analyzed, comprising 283 strains from patients visiting two hospitals in Seongnam and Seoul, Korea, and 180 strains from six hospitals in Tokyo, Japan, between 2018 and 2019. The PVL-encoding genes lukS/F-PV were detected using PCR. Molecular epidemiological and phylogenetic analyses were performed using next-generation sequencing. Overall, 27 (9.5%) PVL-positive MRSA strains were detected among strains isolated from Korea, and 16 (8.9%) were detected among those isolated from Japan. Genotyping of PVL-positive strains revealed that 85.2% of Korean and 81.3% of Japanese strains belonged to USA300. Most USA300 strains from Japan and Korea formed distinct clusters in phylogenetic analyses. Meanwhile, ΨUSA300 and ST22-PT, clones that are prevalent in Japan, were isolated in Korea. This study showed that USA300 strains, which are becoming more prevalent in Japan, are also present in Korea. Furthermore, this study suggests that ΨUSA300 and ST22-PT may be spreading between these two countries. Therefore, it is necessary to continue monitoring the epidemiological trends of PVL-positive MRSA clones both domestically and internationally. IMPORTANCE Panton–Valentine leukocidin (PVL) is a major toxin produced by Staphylococcus aureus . Although a rapid increase in PVL-positive strains has been reported in Japan, data on PVL-positive strains in Korea remain limited. In this study, we performed a comparative analysis of PVL-positive S. aureus isolates from Korea and Japan. The results showed that the clinical backgrounds and genetic profiles of PVL-positive strains isolated in Korea and Japan were highly similar. Furthermore, we confirmed for the first time that clones circulating in Japan, including ΨUSA300 and ST22-PT, were also isolated in Korea. These findings provide valuable insights into the epidemiological status of PVL-positive S. aureus in East Asia.